The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ijoes-07-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Determinants ofShari’ahgovernance disclosure in financial institutions

Abstract: Purpose -This paper aims to investigate factors influencing Shari'ah governance disclosure (SGD) in financial institutions.Design/methodology/approach -Using content analysis approach, 46 annual reports published in 2015 by banks and insurance companies were investigated based on a self-constructed disclosure index.Findings -The results show that the average level of voluntary disclosure of Shari'ah governance in Saudi financial institutions is 11.7 per cent, which is lower than expectations Moreover, regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Therefore, it does not depend on the status of the company, whether it could make a profit or not. Research findings supported the previous studies (Azid & Alnodel, 2018;Samaha et al, 2012). However, there is evidence to suggest that profitability has a positive and significant effect on IGD (Grassa, 2018;Sarhan & Ntim, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it does not depend on the status of the company, whether it could make a profit or not. Research findings supported the previous studies (Azid & Alnodel, 2018;Samaha et al, 2012). However, there is evidence to suggest that profitability has a positive and significant effect on IGD (Grassa, 2018;Sarhan & Ntim, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Azid and Alnodel (2018) and Albassam and Ntim (2017) found the influence of the board composition on shariah governance disclosure. Ownership structure is also a determinant of IGD (Azid & Alnodel, 2018;Grassa, 2018). Islamic banks owned by the government tend to be more obedient.…”
Section: The Concept Of Islamic Governance Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“… Al-Ruithe and Benkhelifa (2020) explored the factors for implementing cloud data governance in the Kingdom of Saudi Arabia (KSA). Azid and Alnodel (2019) examined Shari'ah governance disclosure in financial institutions in KSA. Sian et al.…”
Section: Introductionmentioning
confidence: 99%
“…The study investigated the relationship between institutional ownership and the disclosure of IFSB as the institutional shareholders play a significant role in monitoring the management of banks and helping to disclose more details related to products and services that lead the business to better financial results (Grassa et al, 2018). In Saudi Arabia, Azid and Alnodel (2019) found that local financial institutions owned by non-governmental agencies are more likely to voluntarily reveal their Shari'ah governance, especially from the banking sector. Therefore, the following hypothesis is developed:…”
Section: Accounting Experts On the Boardmentioning
confidence: 99%